Analisis Determinan Kualitas Layanan dan Iklan Terhadap Keputusan Nasabah Menggunakan Produk Wadiah Yadhomanah di BRI Syariah Cabang Sipin Kota Jambi - Subhan Subhan (Indonesian Journal of Islamic Economics and Business, 2020)
The more important the quality of service and promotion applied to the company, the management can improve customer decisions. This research is quantitative descriptive. The population in this study were all customers of Bank BRI Syariah Jambi Branch with a total sample of 96 customers. The sampling technique is convenience sampling. The data analysis technique uses multiple linear regression. The results of multiple regression equations, the equation is known, as follows: KN = 16.783 + 0.598 KP + 0.187 PP, which from this equation is known that the variable that has the greatest influence is the Service Quality variable with the level of coefficient (β) of 0.598, then followed by Advertising Products with a coefficient of 0.187. And finally based on the calculation of the coefficient of determination, then the two independent variables simultaneously (service quality and product advertising) studied were able to explain the variable decisions of customers in choosing to save at BRI Syari'ah Bank as much as 15.1%, and the remaining 84.9% was explained by other independent variables not examined in this study.